Between the Impossibilities of the Past and a New Gender Order - Analysing the Professional Trajectories of Portuguese Women Visual Artists - Correia, S.B. (16th Conference of the European Sociological Association - Tension, Trust and Transformation, 2024)
The communication results from an ongoing doctoral research that aims to elucidate the gender dynamics within the Portuguese artistic field, and also to understand how gender shapes the array of opportunities and constraints of visual artists’ professional trajectories. In the qualitative component of the study, the life paths of 43 female artists were delineated through in-depth interviews. Analysing their accounts allowed me to discover what they observe in the field and shed light on how gender impacts their professional endeavours. Despite the identification of instances of gender inequality, many artists contend that their careers are affected by other circumstances, such as the socioeconomic background, the quality of the social network, the randomness of the gatekeepers' decisions or the size and deregulation of the art market. The inequalities in work-life balance are the overarching theme that unifies the representations and practices of the interviewees. Nearly all mothers among them acknowledge a deceleration or even an interruption in their artistic pursuits, attributing this to the demands of motherhood. Those without children admit that the prospect of motherhood is significantly constrained by the idea of professional disappearance and precariousness. The findings of this research provide insight into the experiences of these women, positioning them amid the "impossibilities of the past" (Silva & Leandro, 2013) that persist in relegating them to the peripheries of the artistic field, and a new social (and gender) order that, more recently, appears to animate both artistic structures and women's agency, propelling them towards the coveted centers of recognition.